Assessing the vulnerability of urban public health system based on a hybrid model - Lingmei Fu; Zhirong Wang; Yutao Zhu; Benbu Liang; Ting Qian; Haiyun Ma (Frontiers in Public Health)
BackgroundPublic health emergencies pose direct threats to economic and social development. The vulnerability of urban public health system is a major cause of public health emergency outbreaks. It is essential to assess the vulnerability urban public health system.Materials and methodsTo address the uncertainty inherent to the vulnerability assessment process, a novel hybrid model is proposed. Stage 1 involves the development of an indicator system, incorporating a comprehensive set of vulnerability factors identified through literature review and expert consultation. Stage 2 involves the calculation of indicator weights using the Bayesian best-worst method (BWM)—a novel probabilistic group decision-making approach that incorporates Bayesian statistics with the traditional BWM. Stage 3 involves the determination of vulnerability levels using a cloud model. The cloud model can combine the randomness and fuzziness of assessment to deal with uncertainty. The model is applied to assess the vulnerability of Shanghai's public health system. Moreover, a sensitivity analysis was conducted to validate the effectiveness and robustness of the model.ResultsA total of 18 factors were identified as affecting the vulnerability of the urban public health system. The most significant among them are “poor coordination and cooperation among various personnel,” “insufficient information assurance,” “low public awareness,” and “low competency among staff in relevant departments and institutions.”ConclusionThe proposed hybrid model is both effective and robust. This study contributes to reducing the vulnerability of urban public health systems, thereby enhancing public health risk management in urban settings.